Elements of structure and productivity of clone I-214 (Populus×euramericana (Dode) Guinier) plantations on the river Sava alluvium - Andrašev Siniša; Rončević Savo; Vučković Milivoj; Bobinac Martin; Danilović Milorad; Janjatović Gojko (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2010)
Two experimental plantations of Euramerican poplar (Populus×euramericana (Dode) Guinier) - clone I-214 were researched on the river Sava alluvium in Srem. Three sample plots were established in each of the plantations, aged 31 years. The soil type was humofluvisol (alluvial semigley), planting space 6×6 m. The plantations were established with 278 rooted cuttings per hectare, and the number of trees at the age of 31 accounted for 46.5-60.6%. The constructed height curves, mean stand height (hg) and upper (hg20%) heights show that the study plantations were established on different site classes, which was significantly reflected on other plantation growth elements and productivity. However, there was no significant effect of site class on the variability (sd and cv) and shape of diameter structure (α3 and α4). The constructed models of diameter structure for each site class (by Weibull function) differ by location parameter (a), and do not differ by parameter of scale (b) and shape (c). The tree and plantation growth elements show a high production potential of the clone I-214 which indicates that, on optimal soils and with the provided technological measures in the stage of nursery production and in the stage of plantation establishment, clone I-214 presents the good base for high production effects.